2017
DOI: 10.1016/s2352-3026(17)30027-3
|View full text |Cite
|
Sign up to set email alerts
|

Pacritinib versus best available therapy for the treatment of myelofibrosis irrespective of baseline cytopenias (PERSIST-1): an international, randomised, phase 3 trial

Abstract: CTI BioPharma Corp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(180 citation statements)
references
References 30 publications
2
173
0
2
Order By: Relevance
“…90 Pacritinib, a JAK2/FLT3 inhibitor, also deserves to be tested in proliferative CMML. 132,133 Because activation of the Hedgehog signaling pathway could contribute to the development of leukemic stem cells, CMML patients can be included in a phase 1 study of a smoothened antagonist. 134 Finally, high expression of interleukin-3 receptor (CD123) in leukemic stem cells led exploration of the efficacy of SL-401, a diphtheria toxininterleukin-3 fusion protein, 135 in patients with hematological malignancies including CMML.…”
Section: Currently Explored Therapeutic Strategies In Cmml Patientsmentioning
confidence: 99%
“…90 Pacritinib, a JAK2/FLT3 inhibitor, also deserves to be tested in proliferative CMML. 132,133 Because activation of the Hedgehog signaling pathway could contribute to the development of leukemic stem cells, CMML patients can be included in a phase 1 study of a smoothened antagonist. 134 Finally, high expression of interleukin-3 receptor (CD123) in leukemic stem cells led exploration of the efficacy of SL-401, a diphtheria toxininterleukin-3 fusion protein, 135 in patients with hematological malignancies including CMML.…”
Section: Currently Explored Therapeutic Strategies In Cmml Patientsmentioning
confidence: 99%
“…13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib. 21 Here, we report the outcome of 218 patients after ruxolitinib.…”
Section: Introductionmentioning
confidence: 99%
“…Pacritinib, previously shown to be active in the PERSIST‐1 and PERSIST‐2 studies, is undergoing further development with refinement of optimal dosage . Indeed, the recently published phase 3 study results, in which pacritinib 200 mg twice daily was found to be significantly better than best available therapy, including ruxolitinib, for reducing splenomegaly and clinical symptoms in patients with MF and thrombocytopenia, for both previously untreated and those who had received prior ruxolitinib.…”
Section: Investigational Therapies For Classical Mpns In 2018mentioning
confidence: 99%